Polymorphic behavior during isothermal crystallization of high stearic high oleic sunflower oil stearins - Rincón Cardona, Jaime A. (2013)
The polymorphic phases of two high stearic high oleic (HSHO) sunflower oil stearins obtained by dry and solvent fractionation of the oil with the aim of use them as trans fat replacers or cocoa butter equivalent were studied by performing in situ isothermal crystallization studies following the appearance of polymorphic forms by X-ray using synchrotron radiation. Thermal behavior, equilibrium and actual isothermal solid fat content and morphology of phases were also analyzed. Three polymorphic forms were observed when samples were crystallized at 10 °C/min to different crystallization temperatures (Tc): α, β'2, and β'1. The α form was the first polymorph obtained at all temperatures used and in the opposite way expected, at most crystallization temperatures it did not disappear when β'2 or β'1 forms appeared. β'2 form crystallized below 16 or 23 °C for soft and hard stearins, respectively. Above those temperatures, the obtained polymorph was the β'1 form. The β polymorphs were not obtained during the times selected for isothermal crystallization. However, β2 form appeared at least after 6 h at Tc while after 48 h of storage at 25 °C the β1 polymorph was the main form. The β2 polymorphic form, which is required for chocolate manufacture, has a very short life and was isolated from β1 by applying cooling/reheating cycles. The β1 form was the most frequently observed. Therefore, processing conditions must be carefully controlled to obtain the desired polymorphic form during product manufacturing. This study provides full characterization and quantification of polymorphic phases of HSHO stearins in real time. Results from this study will help optimize processing conditions for the use of HSHO stearins in industrial applications as trans fat replacers and cocoa butter equivalents.